2016
DOI: 10.4187/respcare.04079
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Clinical and Quality of Life Outcomes of Long-Stay ICU Survivors Recovering From Rehabilitation on Caregivers' Burden

Abstract: BACKGROUND: The objective of this work was to evaluate the time course of clinical and healthrelated quality of life outcomes of long-stay ICU survivors' and caregivers' burden. METHODS: The study included 23 subjects of mixed diagnosis (66 ؎ 11 y, body mass index 26.5 ؎ 5.6 kg/m 2 ) with a recent episode of acute respiratory failure needing in-hospital rehabilitation. Subjects and caregivers were evaluated at hospital discharge (T0, n ‫؍‬ 23) and 6 months later (T6, n ‫؍‬ 16). At T0 and T6, subjects' clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Post-traumatic stress disorder (PTSD) and strain are seen in 21% of the caregivers [ 120 ]. A randomized trial, where caregivers provided respiratory physiotherapy at home, showed improvement of the cardiorespiratory status of the patients and their HRQoL (as measured with the EuroQoL 5D methodology) [ 121 , 122 ]. While the majority of the above-mentioned studies were not specifically designed for the very elderly patient group, it seems logical that the perceived strain, depressive symptoms and HRQoL will also translate to this group of caregivers.…”
Section: Long-term Outcomes Are the Best Criteria To Judge Appropriatmentioning
confidence: 99%
“…Post-traumatic stress disorder (PTSD) and strain are seen in 21% of the caregivers [ 120 ]. A randomized trial, where caregivers provided respiratory physiotherapy at home, showed improvement of the cardiorespiratory status of the patients and their HRQoL (as measured with the EuroQoL 5D methodology) [ 121 , 122 ]. While the majority of the above-mentioned studies were not specifically designed for the very elderly patient group, it seems logical that the perceived strain, depressive symptoms and HRQoL will also translate to this group of caregivers.…”
Section: Long-term Outcomes Are the Best Criteria To Judge Appropriatmentioning
confidence: 99%
“…In this issue of RESPIRATORY CARE, Comini et al 20 present interesting findings from their study of physical and psychological outcomes in ICU survivors and strain and information needs in family caregivers at 2 time points: (1) hospital discharge after an in-patient rehabilitation program (n ϭ 23) and (2) 6 months post-hospital discharge (n ϭ 16). The authors also explored relationships between outcomes in ICU survivors and caregivers' strain, defined as the severity of stress experienced by family caregivers.…”
mentioning
confidence: 99%
“…Notably, the study findings suggest that the pace of psychological recovery may not be synchronous with the pace of physical recovery. Comini et al 20 found that, despite notable improvement in physical function, there was no change in perceived quality of life or self-efficacy in the first 6 months post-hospital discharge. Consistent with reports from previous studies, [21][22][23] these findings suggest that the impact of critical illness persists for an extended period of time and even after recovering physical independence, distress from remaining physical symptoms (eg, fatigue) may still be present.…”
mentioning
confidence: 99%
See 2 more Smart Citations